2014
DOI: 10.1021/jo501739j
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective (Diacetoxyiodo)benzene-Promoted Halocyclization of Unfunctionalized Olefins

Abstract: A metal-free method for intramolecular halocyclization of unfunctionalized olefins was detailed. (Diacetoxyiodo)benzene (PIDA) was very effective for haloamidation, haloetherification, and halolactonization of unfunctionalized olefins. In the presence of 1.1 equiv of PIDA and suitable halogen sources, a variety of unfunctionalized olefins could be converted to the corresponding 1,2-bifunctional cyclic skeletons in good to excellent isolated yields, and key intermediates for biologically interesting compounds c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 89 publications
(54 reference statements)
0
54
0
Order By: Relevance
“…In the course of searching for new methods for the amination of CC multiple bonds, we found that the intramolecular fluoroamination of unfunctionalized olefins was possible with BF 3 as the fluorine source and PhI(OAc) 2 as the reaction promoter 12. We assumed that the direct aminoboration of CC double bonds should be possible if an NB intermediate could be generated during the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…In the course of searching for new methods for the amination of CC multiple bonds, we found that the intramolecular fluoroamination of unfunctionalized olefins was possible with BF 3 as the fluorine source and PhI(OAc) 2 as the reaction promoter 12. We assumed that the direct aminoboration of CC double bonds should be possible if an NB intermediate could be generated during the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Liu and coworkers pioneeringly disclosed a regioselective palladium-catalyzed intramolecular oxidative aminofluorination of unactivated alkenes (22), in which AgF was employed as a fluorination reagent in the presence of PhI(OPiv) 2 (Scheme 5). [15] The transformation offered a very efficient method to prepare fluorine-containing cyclic amines (23). To understand the possible reaction mechanisms, deuterium-labeled alkene E-22 a-d1 was subjected to the standard aminofluorination conditions, and the reaction afforded a mixture of trans-23 a-d1 and cis-23 a-d1 in 79% yield with a 72:28 ratio.…”
Section: Amino- Oxy-or Carbofluorination Of Alkenesmentioning
confidence: 99%
“…Similarly, a metal-free intramolecular aminofluorination of unfunctionalized olefins with Et 2 O • BF 3 and PhI(OAc) 2 was detailed. [23] The corresponding fluoroamidation products were obtained only when Et 2 O • BF 3 was employed rather than conventional metal fluorides or other fluorine sources. The reactions finished in minutes and gave the endo 3-fluoropiperidine products as the sole isomers in moderate yields, but with varied amounts of 3-acetoxypiperidines.…”
Section: Amino- Oxy-or Carbofluorination Of Alkenesmentioning
confidence: 99%
“…( R )‐2‐(bromomethyl)‐5‐fluoro‐1‐tosylindoline (7m) . Yield: 30.6 mg, 80%, light yellow solid, mp: 108–109 °C.…”
Section: Figurementioning
confidence: 99%